Meningkatkan Motivasi Belajar Siswa Melalui Media Pembelajaran - Monica Gabriela Nainggolan; Ratih Ayunda; Wahyuni Amanda Hasibuan; Windy Antika (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Learning motivation is the general main drive in students that produces learning practice, ensures learning progress, and guides learning practice to achieve learning goals. The aim of the exam to be achieved is to find out how to increase students' learning inspiration through learning media. This research method uses a subjective system to describe and understand what the use of realization media means for student learning inspiration. Student inspiration can be broadened by utilizing various techniques and media that suit learning targets. There are several examples of systems and media that can be used to increase student learning inspiration, namely true evaluation and accompanying evaluation, character teaching, teachers as solace, intuitive learning methodology, and the use of creative learning media.